Self-regulating dual season clothing / Atiqah Syamimi Faizul Hamimy ... [et al.]. - Faizul Hamimy, Atiqah Syamimi; Mad Zin, Muhammad Zulhakim; Nazri, Nur Nazurah; Rashidi, Nur Syarah Izzati; Mohd Yusri, Nurul Hana Asyiqin (2025)
Wearther Enterprise is a partnership-based company managed by five key roles; Office Manager, Financial Analyst, Marketing Executive, Operations Executive, and Supply Chain Coordinator. Each manager plays an essential role in ensuring the company’s success and fulfilling its objectives. Wearther Enterprise specializes in producing and selling Self-Regulating Dual-Season Clothing, an innovative apparel line designed to provide comfort in both hot and cold climates. This breakthrough clothing incorporates Phase-Change Materials (PCM), which regulate body temperature by absorbing heat to cool the body down in warm conditions and releasing stored heat to keep the body warm in colder weather. Smart design, the clothing features dual-layer fabrics, an insulated layer for warmth and a breathable layer for cooling. It includes adjustable elements, such as reversible sides, making it adaptable to various activities and weather conditions. Premium materials and durability, by embedding high-tech PCM into durable fabrics such as polyester and cotton, the company offers a product that balances functionality, comfort, and longevity. The company is located in Jalan Medan Pusat Bandar 8A, Seksyen 9, 43650 Bandar Baru Bangi, Selangor, targeting individuals aged 18-45 with active lifestyles or those living in areas with unpredictable weather. The product will be marketed at prominent shopping centers across Selangor, a strategic location with a population of over 114,415, ensuring convenient access to potential customers. Despite competition from established brands like M&B, Jalan Jalan Japan, Pusat Fesyen KW, and Sport Planet Warehouse Outlet, Wearther Enterprise views this as an opportunity to distinguish itself through innovation, superior materials, and unique features. The company aims to reach 5% of its target market, approximately 114,415 customers, in its first year by emphasizing quality and functionality.